Effect of SOIAIC on photoionization time delay of the Xe 3d subshell. Issue 15 (January 2020) - Banerjee, S; Deshmukh, P C; Manson, S T
Synopsis: The effect of spin-orbit activated interchannel coupling (SOIAIC) has been studied on the time delay spectrum of 3d photoionization in xenon. The relativistic-random-phase-approximation with relaxation (RRPA-R) has been used to calculate the Wigner-Eisenbud-Smith (WES) time delay in photoionization. SOIAIC has a strong influence on the WES time delay for all ejection angles of the photoelectrons with respect to the incident direction and the polarization vector of the photon absorbed.